AGE, TOTAL PSA, PSA DENSITY AND GLEASON SCORE, TAUS AS PREDICTIVE FACTORS IN PATIENTS WITH PROSTATE CANCER - Albar, Daruqutni; Rochadi, Sungsang (Indonesian Journal of Urology, 2016)
Objective: To find the factors related as predictive factors for Gleason score in prostate cancer patients. Material & methods: This study obtained a total sample of 144 patients with prostate cancer in Sardjito General Hospital Yogyakarta in 2009-2013. Of the total 144 patients, only 64 patients had complete medical records. All patient samples were patients who had biopsy of the prostate. This study is a retrospective case-control study to predict the Gleason Score in patients with prostate cancer in terms of age, total prostate specific antigen (PSA), PSA density and TAUS. Normality test assessed the distribution of the data. Pearson test assessed normal distribution and Spearman test for normal distribution. All data were analyzed using SPSS version 18. Results: Analysis of data from 64 patients with prostate cancer with a normal distribution of the variables obtained on age and TAUS with p > 0.05 whereas abnormal distribution obtained on total PSA, PSA density with p < 0.05. Of the data on the data with a normal distribution, age and TAUS with values obtained p 0.039 and p 0.738. From these data it can be said there is a relationship between age and Gleason score where the higher the age the higher the Gleason score. TAUS of the data can be said there is no relationship between TAUS and Gleason score. Then the abnormal distribution of the data obtained with a total PSA p < 0.001 and PSA density p < 0.001. The data is obtained from the relationship between total PSA and PSA density with Gleason score. Conclusion: It was found that age, total PSA, PSA density affect the increase in Gleason score where the higher the age, total PSA and PSA density the higher the Gleason score in patients.